Assessing Vaccine Herd Protection by Killed Whole-Cell Oral Cholera Vaccines Using Different Study Designs - Ali, Mohammad; Clemens, John (Frontiers in Public Health, 2019)
The population level effectiveness of a vaccine may arise as the result of direct protection of vaccinees and vaccine herd protection, which may protect non-vaccinees, vaccinees, or both. Indirect, total, enhanced and overall vaccine protection are measures of vaccine herd protection. The level of population level effectiveness induced by a vaccine depends on many factors, including the level of vaccine protective efficacy, the magnitude and distribution of vaccine coverage at a point in time and the extent to which different groups mix with one another in the community. Data on vaccine herd protection are important in the assessment of the public health importance and cost-effectiveness of many vaccines. Killed whole-cell (WC) oral cholera vaccines (OCVs) have been evaluated for herd protection in various study settings, leveraging geographic information system (GIS) tools for the analyses. This article provides a brief description of the herd protective effects of killed WC OCVs measured using various study deigns that include a) individually randomized, controlled clinical trials, b) cluster randomized clinical trials, c) observational cohort studies, and d) observational case-control studies. In all of the study designs, significant herd protection was observed in unvaccinated persons as well as in the community as a whole. The findings of these studies suggest that using killed WC OCV as a public health tool for controlling cholera is impactful and cost-effective.